Asy-Syakhshiyatu Al-Sardiyatu Wa Tamtsilatuha Fi Thali’ati Kutubi al-Adabi al-Abbasi - Elsayed Mohamed Salem Alawadi (IJAS: Indonesian Journal of Arabic Studies, 2020)
Literature of its two kinds reached, during the Abbasid era, to the peak of goodness and splendor, whereby the mingling of Arabs with non-Arabs had its far-reaching impacts in refining the ideas and imagination, the maturity of culture, and improving the types of speech; poetry and prose. The narrative discourse took its best chance when the literary arts diversified in that era, and the narration should not be without a time in which events are narrated and characters revolve in its orbit. Hence this study came to shed light on narrative characters because it is the column of narrative narrative construction, and to show the types of narrative characters, and follow these different types of characters in samples from the early books of narration, such as "Fun and Familiarity”, “The Animal”, “The Statement and Clarification”, the “Calella and Damnah” and “Women's News”, using the descriptive and the analytical approaches, and thus To explore his gore and to discover its essence.لقد وصل الأدب بنوعيه في العصر العباسي إلى ذروة حُسنه وروعته؛ حيث كان لامتزاج العرب بالأعاجم آثاره البعيدة في تهذيب الأفكار وثقل الأخيلة ونضج الثقافة وتجويد ألوان الكلام من شعر ونثر، وقد أخذ الخطاب السردي حظه الأوفر حينما تنوعت الفنون الأدبية في ذلك العصر، ولا يتصور أن يكون هناك عمل سردي دون وجود العنصر الحيوي الذي يقوم بالأحداث أو تقع عليه الأحداث، ألا وهو الشخصيات؛ فالشخصيات السردية هي أهم مكونات العمل السردي، وهي العنصر الفعال فيه. ومن هنا جاءت هذه الدراسة لإلقاء الضوء على الشخصيات السردية باعتبارها عمود البناء الروائي القصصي، ولبيان أنواع الشخصيات السردية، وتتبع تلك الشخصيات بأنواعها المختلفة في مختارات ونماذج من  كتب السرد الحكائي العباسي؛ ككتاب "الإمتاع والمؤانسة" و"الحيوان"، و"البيان والتبيين"، و"كليلة ودمنة" و"أخبار النساء"، باستخدام المنهج الوصفي التحليلي، ثم الاستنباطي لسبر غوره وتبيين جوهره.